Risk of dementia in Nepal: A cross-sectional survey in mountainous, hilly, and lowland regions - Bibha Simkhada; Sanju Thapa Magar; Padam Simkhada; Pasang Tamang; John Stephenson (PLoS ONE, 2025)
Introduction Globally dementia is a growing public health problem, with over 135,000 people in Nepal living with dementia. Nepal lacks national and community-based data on dementia prevalence. This study aims to determine the dementia risk in Nepal and assess the effects of age, sex, and geographical location on disease prevalence. It also intends to inform policy makers about the burden of dementia, prompting them to plan and prepare appropriate health and social care services for individuals affected by dementia. Methods A cross-sectional survey of 933 older people (aged 60 years and over) was conducted to determine the prevalence of suspected cognitive impairment or dementia risk in three geographical regions of Nepal. The Rowland Universal Dementia Assessment Scale (RUDAS) was used to measure cognitive impairment. The study evaluated the overall prevalence of suspected cognitive impairment or risk of dementia and subgroups by region, age group, and sex. Chi-squared tests and multiple logistic regression analyses were conducted to assess the effects. Results 53.7% (501) participants had cognitive impairment or risk of dementia, with slightly higher rates in women (56.5%) than men (51.7%). Cognitive impairment prevalence increases with age and region, with hilly and mountainous areas and low-lying regions having a greater geographic effect. Conclusions There is high risk of dementia in Nepal. The risk is influenced by age and geographical regions, necessitating early diagnosis and tailored interventions for older people and who are residing in higher altitude areas. Policies implemented to address this issue should prioritise community awareness and early screening and diagnosis to reduce complications from dementia. National-level studies and exploration of factors affecting early dementia diagnosis are needed.